Diversity and activity patterns of medium and large terrestrial mammals in the Lapa Verde Wildlife Refuge, Heredia, Costa Rica - Mattey Trigueros , Alejandro (2022)
[Introduction]: Wildlife refuges are crucial to improve connectivity in the context of biological corridors, as they conserve forest patches and consequently neotropical mammal populations. However, in order to devise conservation and management strategies, it is a priority to carry out field studies that validate these efforts and measure their effectiveness over time. [Objective]: To generate baseline information on the population status of medium and large terrestrial mammals and their activity patterns to help the management and protection of the Lapa Verde Wildlife Refuge. [Methods]: We analyzed the camera-trapping methodology by placing 13 camera traps per sampling block, divided into two blocks (1 855 ha) during January-February 2015 and December 2015-January 2016. [Results]: The sampling effort was 1 584 nights, capturing 18 species with the presence of large and medium predators such as Panthera onca, Canis latrans, Leopardus pardalis, and Leopardus wiedii, as well as species of prey such as Silvilagus sp., Dasypus novemcinctus, Dasyprocta punctata, and Cuniculus paca. The species with the highest RAI was D. punctate. The richness was similar between blocks. However, the patterns of circadian activity differed between some species (L. pardalis and D. punctata). [Conclusions]: Species such as jaguars and tapirs, which require large areas of land to settle, use these conservation blocks; this indicates the importance of the conservation of these blocks.